PENERAPAN MODEL PROBING-PROMPTING DALAM MENINGKATKAN HASIL BELAJAR MTs BHAYANGKARA TALLO MAKASSAR - ramadani, suci; Ahmad; ratika; mustamin; andi hasriani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The effectiveness of the learning process greatly determines the success of achieving learning objectives. However, low student confidence in actively participating and providing feedback is a common obstacle. This is often caused by ineffective learning methods and less than optimal student involvement, which has a negative impact on their learning achievement. Therefore, this study examines the implementation of the Probing-Prompting learning model as a potential solution to improve learning outcomes. This study aims to answer two main questions: (1) How is the implementation of the Probing-Prompting learning model in class VII B MTs Bhayangkara Tallo Lama Makassar? (2) How effective is the Probing-Prompting model in improving the Fiqh learning achievement of class VII B MTs Bhayangkara Tallo Lama Makassar students. This Classroom Action Research (CAR) was conducted in class VII B MTs Bhayangkara Tallo Lama Makassar. Data collection was carried out through various methods, including observation, interviews, tests, and documentation. The results of the study showed a significant increase in the implementation of the Probing-Prompting model during two cycles. Both teacher and student activities experienced significant improvements, both in terms of the process and learning outcomes. The study was stopped in cycle II because substantial improvement had been achieved. Data analysis showed an increase in the percentage of students who achieved the Minimum Completion Criteria (KKM). In the pre-cycle, only 11 students (36.67%) achieved the KKM. This number increased to 17 students (56.67%) in cycle I and reached 26 students (86.67%) in cycle II. These results show the effectiveness of the Probing-Prompting model in improving students' Fiqh learning achievement.